Pengaruh Model Pembelajaran Problem Based Learning Terintegrasi High Order Thinking Skill terhadap Kemampuan Berpikir Kritis dan Sikap Percaya Diri - Inang Irma Rezkillah; Haryanto Haryanto (Universitas Syiah Kuala, 2020)
This study aims to identify: (1) the impact of high order thinking skill integrated problem based learning on critical thinking skill; (2) the impact of high order thinking skill integrated problem based learning on student self-esteem; (3) the influence of high order thinking skill integrated problem based learning has both the critical thinking skill and self-esteem together. This study is an experimental quasi study with a pretest-posttest control design. The populationsof this study were the wholestudents of Primary School Teacher Education in the 4th semester of Ahmad Dahlan University by the year 2020/2021. This research used a random sampling technique. The data were analyzed using independent t-test and MANOVA, and Hoteling’s Trace test.The results showed that (1) there was an influence of HOTS integrated PBL that there are critical thinking skills; (2) there is an influence of HOTS integrated PBL that there is the confidence of the students; (3) there is an influence of HOTS integrated PBL that there arecritical thinking skills and confidence together